Makna Motivasi pada Lirik Lagu Tasna’ul Mustahil karya Hamza Namira dan Humood Al-Khudher (Studi Analisis Semiotik Rolland Barthes): The Motivational Meaning of the Lyrics of the Song Tasna'ul Mustahil by Hamza Namira and Humood Al-Khudher (Rolland Barthes Semiotic Analysis Study) - Ridlo, Akhmad; Lisna; Asep Sopian (Universitas Negeri Semarang, 2024)
This study aims to determine the meaning of motivation contained in the lyrics of the song Tasna'ul Mustahil by Hamza Namira and Humood Al-Khudher. This song was chosen as the object of research because it is considered to have the potential to convey motivational messages to its listeners, especially young people and Gen Z, who currently often experience overthinking, burnout, self-discovery, and mental health. In this research, the author uses descriptive and qualitative research methods. The theory used in this research is Rolland Barthes' semiotic theory. The results showed that the lyrics of the song